1998
DOI: 10.1056/nejm199802053380602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Protective-Ventilation Strategy on Mortality in the Acute Respiratory Distress Syndrome

Abstract: As compared with conventional ventilation, the protective strategy was associated with improved survival at 28 days, a higher rate of weaning from mechanical ventilation, and a lower rate of barotrauma in patients with the acute respiratory distress syndrome. Protective ventilation was not associated with a higher rate of survival to hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
1,927
5
238

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,202 publications
(2,205 citation statements)
references
References 40 publications
35
1,927
5
238
Order By: Relevance
“…were included in the final analysis. As a result of a meta‐analysis involving studies in which the influence of non‐PEEP interventions could not be ignored,203, 207, 211, 212 no significant difference in mortality rate was observed in the high PEEP group in comparison with the low PEEP group (risk ratio: 0.87, 95% CI: 0.74–1.02). In addition, when focusing the analysis on moderate or severe ARDS cases (PaO 2 /FiO 2 ratio ≤200 mmHg), the results of both the sub‐analyses including the studies permitting non‐PEEP interventions as well as the sub‐analyses excluding such interventions indicated that the high PEEP group exhibited a significantly lower mortality rate than the low PEEP group (risk ratio: 0.82, 95% CI: 0.73–0.92, risk ratio: 0.85, 95% CI: 0.75–0.96, respectively).…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…were included in the final analysis. As a result of a meta‐analysis involving studies in which the influence of non‐PEEP interventions could not be ignored,203, 207, 211, 212 no significant difference in mortality rate was observed in the high PEEP group in comparison with the low PEEP group (risk ratio: 0.87, 95% CI: 0.74–1.02). In addition, when focusing the analysis on moderate or severe ARDS cases (PaO 2 /FiO 2 ratio ≤200 mmHg), the results of both the sub‐analyses including the studies permitting non‐PEEP interventions as well as the sub‐analyses excluding such interventions indicated that the high PEEP group exhibited a significantly lower mortality rate than the low PEEP group (risk ratio: 0.82, 95% CI: 0.73–0.92, risk ratio: 0.85, 95% CI: 0.75–0.96, respectively).…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
“…As a result of the systematic review, only six 2013 Cochrane Review202‐adopted RCTs191, 203, 204, 205, 206, 207 involving the use of lung protective ventilation methods focusing primarily on low tidal volume in adult ARDS patients were identified. Mortality statistics were reported in all six studies ( n  = 1,305), and while there was a difference in the follow‐up period, this period tended to be shorter in the low tidal volume group (risk ratio: 0.84, 95% confidence interval [CI]: 0.67–1.07).…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
“…Application of Positive End-Expiratory Pressure (PEEP) is one of the most important intervention in managing a patient with ARDS [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have been shown to reduce mortality in some cases [7,6]. However, there are still no well accepted and defined general procedures that can effectively optimize individual ventilator settings over broad cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, as a reaction to the high volumes and pressures applied during mechanical ventilation, the term "protective ventilation" [1][2][3] has been introduced. In our opinion, this expression is, however, deeply misleading, as the mechanical ventilation does not protect the lung from the development of the acute respiratory distress syndrome (ARDS), but simply aims to protect it from avoidable damage due to harmful ventilatory settings.…”
mentioning
confidence: 99%